2003
DOI: 10.1002/jbm.a.10041
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic differentiation of cultured rat and human bone marrow cells on the surface of zinc‐releasing calcium phosphate ceramics

Abstract: Rat and human bone marrow cells (BMCs) were cultured on a composite ceramic of zinc-containing beta-tricalcium phosphate and hydroxyapatite (ZnTCP/HAP) with a (Ca+Zn)/P molar ratio of 1.60 and varying zinc contents. After a 2-week culture of the BMCs in the presence of beta-glycerophosphate and dexamethasone, many macroscopic mineralized areas with high alkaline phosphatase (ALP) activity were seen on the ZnTCP/HAP ceramic disks. The ALP activity increased with increasing zinc content in the ceramics. The high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 25 publications
8
68
0
Order By: Relevance
“…The Ca/P composition ratio of the mineral-like tissue was 1.63 which corresponds well with the biological hydroxyapatite value (Figure 7b). These results show that mineralization was not affected by the ZnAl 2 O 4 composition of the films and the mineral deposition enhance was in concordance with previous studies of zinc-containing biomaterials that had shown an osteoconductive material for bone-related tissue engineering applications [40][41][42][43] .…”
Section: Resultssupporting
confidence: 92%
“…The Ca/P composition ratio of the mineral-like tissue was 1.63 which corresponds well with the biological hydroxyapatite value (Figure 7b). These results show that mineralization was not affected by the ZnAl 2 O 4 composition of the films and the mineral deposition enhance was in concordance with previous studies of zinc-containing biomaterials that had shown an osteoconductive material for bone-related tissue engineering applications [40][41][42][43] .…”
Section: Resultssupporting
confidence: 92%
“…These findings are in line with the finding of Ito et al, who observed that both rat and human bone marrow stromal cells (BMSc) cultured on zinc-containing BCP differentiated into osteoblast-like cells more than cells on zinc-free ceramics [135]. Elevated zinc released in the medium would potentially play an important role in cell differentiation since it has been reported that supplementing zinc in the medium significantly increases the osteogenic differentiation of both rat and human BMSc [198]. Thus, it is possible that blood/bone marrow stem cells homing to the implantation site due to the inflammatory foreign body reaction may have infiltrated the materials and then differentiated into osteoblasts due to elevated zinc released by the ceramics.…”
Section: Discussionsupporting
confidence: 91%
“…Since the osteogenic differentiation of mesenchymal stem cells can be promoted by trace elements in vitro [198,199], we hypothesise that their addition in calcium phosphate-based materials can result in inductive bone formation. As the incorporation of these elements will also change the physical parameters of the calcium phosphate material (e.g.…”
Section: Aim Of the Thesismentioning
confidence: 99%
“…82) An implant of the zincdoped calcium phosphate ceramics significantly raised the cortical bone apposition rates of the femora of osteoporosismodeled rats. 83), 84) The zincdoped calcium phosphate ceramics were not absorbed due to the suppressive effects of the released zinc ions to osteoclasts in the area directly contacting the bone tissues.…”
Section: )mentioning
confidence: 99%